Passive ownership and long-term orientation around the world - Tobias Ruf (Junior Management Science (JUMS), 2023)
The recent growth of passive investors led to concerns regarding their economic impact. This thesis investigates the influence of passive investors on the long-term orientation of their portfolio firms by using global panel data of publicly listed firms from 2000 to 2019. To tackle endogeneity concerns an instrument variable approach with MSCI All Country World Index membership as the instrument is applied. I find that exogenous increases in passive ownership enhance long-term investment in tangible assets, human capital, and organizational capital. While my results suggest that capital expenditures, number of employees, staff cost, and selling, general & administrative expenses are positively connected with higher passive ownership, I find no evidence for an effect on research & development expenses and average staff costs. In additional analyses I find the effect of passive investors to be time-variant and dependent of a firm's country of origin. My findings suggest that passive investors globally foster long-term orientation in their portfolio firms.
Keywords: 650; Passive investors; Index funds; Long-term orientation; Innovation; Instrumental variables estimation